2016
DOI: 10.1016/j.ijcard.2016.01.147
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring potential mortality reductions in 9 European countries by improving diet and lifestyle: A modelling approach

Abstract: BackgroundCoronary heart disease (CHD) death rates have fallen across most of Europe in recent decades. However, substantial risk factor reductions have not been achieved across all Europe. Our aim was to quantify the potential impact of future policy scenarios on diet and lifestyle on CHD mortality in 9 European countries.MethodsWe updated the previously validated IMPACT CHD models in 9 European countries and extended them to 2010–11 (the baseline year) to predict reductions in CHD mortality to 2020(ages 25–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Previous studies provided reductions in total mortality in the range of 0–18% [ 31 ], or 6–10% [ 19 , 40 ] associated with global livestock or red meat reduction consumption. Other studies have evaluated the impact of hypothetical change in specific nutritional factors, such as saturated fats intake, leading to reductions in cardiovascular burden in the range of 6–10% in 9 European countries [ 42 ] and of 14% by 2025 in Sweden [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies provided reductions in total mortality in the range of 0–18% [ 31 ], or 6–10% [ 19 , 40 ] associated with global livestock or red meat reduction consumption. Other studies have evaluated the impact of hypothetical change in specific nutritional factors, such as saturated fats intake, leading to reductions in cardiovascular burden in the range of 6–10% in 9 European countries [ 42 ] and of 14% by 2025 in Sweden [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the reductions in red meat consumption we propose are compatible with a Mediterranean-type diet, which indicates a variety of proteins (meat and poultry, fish, milk and dairy products, legumes) and does not suggest radical choices, such as the adoption of a vegetarian or vegan diet [ 27 ]. For example, diets with fewer animal-sourced foods typically include more legumes, nuts and whole grains which evidence suggests have health benefits and are likely to increase the number of avoided deaths [ 31 , 40 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore risk factor reduction strategies are critical for reducing the CVD burden. Numerous modelling studies have estimated that population-wide risk factor reductions can bring substantial decreases of CVD burden 8,105,106,107 even taking into account current trends of obesity and diabetes. It has also been shown that mortality trends respond very rapidly to changes in risk factors at the population level.…”
Section: Tracking Of Childhood Cvd Risk Factors and Their Determinantmentioning
confidence: 99%
“…7 The potential impact of implementing risk-factor reduction policies focused on diet and lifestyle in 9 European countries has been recently quantified and it was estimated that it would result in up to 29.1% fewer CVD deaths by 2020. 8 However, there is increasing evidence that cardio-metabolic risk in adulthood is partially determined by the same risk profile in childhood. 9 Therefore interventions that target risk factors in young people could potentially be key aspects of preventive strategies in the longterm.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary pattern was not independently related to CVD reduction in the current study. Several studies have identified dietary pattern 174,183,184 as a CVD risk factors. However, some studies failed to reveal the association.…”
Section: Discussionmentioning
confidence: 99%